The Decision Support System of Students Recruitment as Teacher Candidates using Multilevel Multi Attribute Utility Theory (MAUT) - Wahid, Abdul; Muharram, Muharram; A. Rauf, Bakhrani; Agung, Muhammad; Yohandri, Yohandri; Baharuddin, Baharuddin; Sila, I Nyoman; Suyanta, Suyanta (Association for Scientific Computing, Electronics, and Engineering (ASCEE), 2022)
Recruitment is an important aspect of human resource management at a university, particularly at Makassar State University. Selection is a step in the recruitment process that determines whether prospective students who apply are a good fit for the program of study. The advancement of information systems facilitates the recruitment registration process. The decision support system is present to assist decision-makers in receiving appropriate recommendations for prospective teacher students who have been selected. This study employs the MAUT method's development, which is carried out in stages, hence the Multi-Level MAUT. Because assessment metrics are classified, we combine several MAUT methods to reach a final decision. The algorithm used produces good results, namely the ability to rank correctly based on stakeholder preferences.